Impact of hydroxychloroquine on disease progression and ICU admissions in patients with SARS-CoV-2 infection - Awad, Nirvana (Am J Health Syst Pharm, 2021)
DISCLAIMER: In an effort to expedite the publication of articles related to the COVID-19 pandemic, AJHP is posting these manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. PURPOSE: To evaluate whether use of hydroxychloroquine was associated with a reduced likelihood of intensive care unit (ICU) admission in patients with coronavirus disease 2019 (COVID-19) in the early weeks of the pandemic. METHODS: A retrospective, observational, cohort study was conducted to determine selected treatment outcomes in 336 patients hospitalized with COVID-19 at an acute care, community hospital in the Hudson Valley region of New York from March 20 to April 20, 2020. Eligibility included admission to the hospital, a laboratory-confirmed diagnosis of SARS-CoV-2 infection, and no need for intubation or intensive care at admission. The median (interquartile range) ages of patients who received hydroxychloroquine (n = 188 ) and those who did not (n = 148) were 68 (58-82) and 64 (51-73) years, respectively. In a multivariable model that included age, gender, obesity, diabetes, and hydroxychloroquine use, patients who received hydroxychloroquine were significantly more likely than those not treated with the drug to be transferred to an ICU (odds ratio, [OR], 8.1; 95% confidence interval [CI]: 3.8-17) and significantly more likely to be intubated (OR, 7.99; 95% CI, 3.76-16.91); these associations were not influenced by disease severity. In-hospital mortality did not differ significantly with disease severity between those who did and those who did not receive hydroxychloroquine. CONCLUSION: Hydroxychloroquine use was significantly associated with increased risks of ICU admission and intubation in patients with mild, moderate, and severe symptoms of COVID-19. There were no significant between-group differences in mortality with use vs nonuse of hydroxychloroquine.